The prospective associations between problematic gaming and phubbing among Chinese adolescents: Insights from a cross-lagged panel network model - Su, Yingying; Chen, Yan; Gai, Qian; Meng, Xiangfei; Gao, Tingting (Comprehensive psychiatry, 2025)
Previous studies are limited in addressing the directionality of temporal relationships between problematic gaming and phubbing symptoms by exploring cross-sectional studies. Therefore, we estimated the longitudinal relationships between individual behavioral addictive symptoms including problematic gaming and phubbing in adolescence, and explored potential sex differences in these relationships. This study included 3296 participants in Shandong Province, China. Data were collected from November 2021 (mean [SD] age: 15.17 [1.44] years) to May 2023 (mean [SD] age: 17.50 [1.18] years), with females comprising 54.5 % of the sample. Problematic gaming and phubbing were assessed using validated scales at each wave. We construct cross-sectional networks and cross-lagged panel networks (CLPN) to explore the contemptuous and temporal relationships between problematic gaming and phubbing. Contemporaneous networks revealed significant differences in problematic gaming and phubbing networks between males and females. Additionally, temporal network analyses indicated that among male adolescents, feeling anxious when unable to play games was the most influential predictor of subsequent behavioral addictive symptoms. For female adolescents, fantasizing about gaming had the most significant associations with future addictive behaviors. The strongest bridge symptom linking problematic gaming and phubbing for both sexes was focusing on phones rather than engaging in conversation. The study applied network modeling to panel data from a large, population-based cohort of adolescents, identifying unique longitudinal relationships between problematic gaming and phubbing across symptom domains. It provides valuable insights into the characterization of behavioral addictive symptoms among adolescents and the potential predictive relationships among these symptoms among different sexes, guiding sex-specific targeted interventions for adolescents. •Distinct problematic gaming and phubbing networks were observed between male and female adolescents.•Anxiety from lack of gaming predicts future addictive behaviors in male adolescents.•Gaming fantasies most significantly influence future addiction in female adolescents.•Phone-centric behavior links problematic gaming and phubbing across both sexes.•Findings support sex-specific interventions for adolescent behavioral addictions.